Analisis Komparatif Sinkronis Bahasa Sunda dengan Bahasa Jawa Dialek Desa Panjalin Kidul Kabupaten Majalengka - Novia Rahmawati; Ratnawati (JALADRI : Jurnal Ilmiah Program Studi Bahasa Sunda, 2023)
This research aims to find out the kinship of Sundanese language with Javanese language of Panjalin Kidul dialect. The research method used is desciptive qualitative method. Data collection was done using the method of chapping and listening. The instrument used in the data collection process was a Sundanese vocabulary list. The data analysis method used is the synchronic comparative method. This research was conducted in Panjalin Kidul Village, Majalengka Regency, West Java Province. The results of this study showed that 84 data were obtained that were related based on the symptoms of language sound variation from 160 vocabularies. With 68 data of synonym language sound variation and 16 data of homonym language sound variation. The level of kinship between Sundanese and Javanese is 80% with an error term to determine the percentage of kinship of 8,6. Therefore, it can be concluded that Sundanese and Javanese dialects of Panjalin Kidul Village have a language kinship with a percentage of 80% and show an interesting attraction between the two languages.